Change Management in Implementing the SAMR Model as a Learning Transformation Tool for Teachers at MA Darunnajah - Sholeh, Muh Ibnu; Ab Rahman, Siti Fatinnah binti; Sokip, Sokip; Syafi’i, Asrop (The Magister of Islamic Education IAIN Pontianak, 2023)
This research to analyze how the SAMR model can be applied to improve the quality of learning at MA Darunnajah. This study used qualitative research methods. The research location MA Darunnajah. Data obtained through observation, in-depth interviews with teachers, students and school staff, analysis of curriculum documents. Checking the validity of the data uses triangulation, source triangulation, data triangulation and technical triangulation. The collected data was analyzed using qualitative analysis methods which generally consist of the process of transcription, coding, grouping essence research results that have the same meaning, and presenting the data. The research results show that change management plays a crucial role implementing the SAMR Model learning transformation tool for teachers at MA Darunnajah. Effective communication between school management and teachers well psychological support has proven effective building understanding change and helping teachers overcome resistance. However the research highlights need for increased training, with teachers suggesting additional training on the SAMR Model and educational technology. potential solution involves providing additional counseling resources to overcome resistance to change. These findings indicate the need for more effective change management, ongoing training, and adequate psychological support to successfully integrate the SAMR Model in teaching that has a positive impact on the quality of education at MA Darunnajah.